KONTRIBUSI KELENTUKAN PERGELANGAN TANGAN DAN KOORDINASI MATA TANGAN TERHADAP AKURASI SERVICE - Finola, Monicha Aulia; Afrizal, Afrizal; Masrun, Masrun; Haryanto, Jeki (Journal of Sport and Exercise Science, 2020)
This study aims to determine the contribution of wrist flexibility and hand eye coordination to the ability to service accuracy. This research is a type of correlational research. This study used 20 PTM Gempas Pauh Sic ring tennis athletes as the population. The sample consisted of 20 people with the sampling technique using saturated / census samples. This research uses wrist flexibility test, tennis ball throw test for hand eye coordination, and service accuracy test is done with service accuracy capability. Analysis of research data using the product moment correlation analysis technique (simple correlation and multiple correlation) with a significant level of ? = 0.05. The results of the study were 1) There was a relationship between wrist flexibility and service accuracy in table tennis for the PTM Gempas Pauh Sic ring athletes. 2) There is a relationship between hand eye coordination and service accuracy in table tennis for PTM Gempas Pauh Sic ring athletes. 3) There is a joint relationship between wrist flexibility and hand eye coordination on service accuracy in table tennis for PTM Gempas Pauh Sic ring athletes.